Biodiesel de soja: taxa de conversão em ésteres etílicos, caracterização físico-química e consumo em gerador de energia Biodiesel from soybean: characterization and consumption in an energy generator - Roseli Aparecida Ferrari; Vanessa da Silva Oliveira; Ardalla Scabio (Química Nova, 2005)
Biodiesel was produced by the transesterification of neutral soybean oil and anhydrous ethanol using NaOH as catalyst. Combinations of biodiesel and diesel in the proportions of 0, 5, 10, 20, 40, 60, 80 and 100% were tested, respectively, as fuel in an energy generator. The average consumption and mixture performance were analysed. The tests showed a reduction in Diesel oil consumption when mixed with up to 20% of biodiesel. The quality characteristics of these fuels were analyzed.